The growth performance and genotoxicity effect of dietary Aloe vera on Oreochromis niloticus juveniles - Simeon Oluwatoyin Ayoola; Hubaidat Oyinkansola Ishola (Aceh Journal of Animal Science, 2020)
Growth and all activities of fish depend significantly on the food they consume.  However, with the rising price of conventional feedstuffs, there is a need to investigate less expensive and readily available plant source as an additive. This research is designed to study the effect of dietary Aloe vera on the growth performance of Oreochromis niloticus juveniles (41.71±0.78g) and its effect on genotoxicity (MN: Micronucleus; LB: Lobed; BD: Bud; BL: Blebbed; BN: Binucleated; NT: Notched).  This research investigated the growth performance and genotoxicity activity of Oreochromis niloticus juveniles in a tank culture system.  Aloe vera (fine powder) was used as a test ingredient in the feed formulation at five inclusion levels (T1 = 5g, T2 =10g, T3 =15g, T4 =20g, T5 =25g) and the Control diet (C0) without the test ingredient.  Test diets were fed to Oreochromis niloticus juveniles, and each diet was assigned to the treatments and control overall in triplicates.  Feeding with test diets was for twelve (12) weeks at 5% of their total body weight daily, which was divided into two and administered at 8 hrs and 16 hrs.  The result showed that the highest growth rate (10.99 ± 5.49g) and the lowest FCR (0.68 ± 0.08) were recorded in the fish fed with the Control diet (C0).  Better growth and nutrient utilization were achieved at low inclusion levels of Aloe vera, at 5g(T1) (8.98 ± 4.49) and 10g (T2) (6.73 ± 3.28) compared to the higher levels of incorporations of the test ingredient. The mean pH and temperature (°C) and dissolved Oxygen level mg/L are 6.50±0.30, 26.3±0.60 and 4.48±0.52mg/L respectively. The  values  of  micronuclei  for  the  cultured  Oreochromis  niloticus  juveniles  were  recorded  to  be  (T1 = 5.50 ± 0.50, T2 = 2.00 ± 1.00, T3 = 2.00 ± 0.00, T4 = 2.50 ± 1.50, T5 = 4.00 ± 1.00, and C0 = 7.00 ± 2.00).  Nuclear  abnormalities  were  recorded  in  T2  (BD = 1.00 ± 0.00),  T3  (NT = 1.00 ± 0.00),  T4  (BD = 1.33 ± 0.47,  BN = 3.33 ± 0.47),  and  T5  (BN = 5.33 ±  0.47,  LB = 3.00 ± 1.00,  BL = 1.67 ± 0.47) . However, no abnormality was recorded in the fish fed with the Control diet (C0). This result showed that the slight addition of this Aloe vera to the diet of Oreochromis niloticus would enhance productivity.